Effect of Food Safety Education on Knowledge, Attitude, and Behavior of School Community and Retail Community in Ampibabo Sub-district - Jamaluddin; Mutiawati, Nur; Mallisa, Samaal (Tadulako Science and Technology Journal, 2024)
Food safety is a condition to prevent food from possible biological, chemical, and other contaminants that can harm and endanger human health. This study was conducted to determine the effect of food safety education on the knowledge, attitudes, and behavior of the school community and retail community before and after the intervention. This type of research is an experimental study with a total sample of 60 people from the school community and 54 people from the retail community. This research began in March-October 2021. The analysis used in this study was the Wilcoxon analysis with the SPSS application. The results of the effect of food safety education on the school community in aspects of knowledge, attitudes, and behavior with the value of Sig. (2 tailed) < 0.05 consecutively 0.030 < 0.05; 0.000 < 0.05 and 0.000 < 0.05. H0 is rejected so that there is an effect of food safety education on food safety knowledge, attitudes, and behavior. The effect of food safety education on the retail community on the knowledge aspect with a value of 0.000 < 0.05, which means that there is an effect of food safety education on the knowledge aspect of the retail community. While on the aspect of attitude and behavior aspect with the value of Sig. (2-tailed) < 0.05 0.106 > 0.05 and 0.363 > 0.05, which means that H0 is accepted, so there is no effect of food safety education on aspects of attitude and behavior in the retail community. The conclusion obtained is that there is an effect of food safety education on the knowledge of attitudes and behavior of the school community, there is an influence towards a better direction after food safety education is carried out on aspects of knowledge of the retail community and there is no effect of conducting food safety education on aspects of attitudes and behavior of the retail community.